The mechanism of short-chain fatty acid in hypertriglyceridemic pancreatitis - Li, Tingting; Deng, Fuyu; Xiong, Jiong; Wu, Fangqi; Tang, Songxun; Zhang, Yijie; Zhang, Qiyong; Song, Jian; Li, Yi; Liu, Xu; Tang, Yan (Frontiers in Microbiology, 2026)
IntroductionThe incidence of hypertriglyceridemia pancreatitis (HTGP) has been rising annually with a poor prognosis, and its pathogenesis is complex. In recent years, the role of gut microbiota and short-chain fatty acids (SCFAs) has gradually attracted attention in HTGP. Therefore, the aim of this study was to investigate the characteristic alterations in gut microbiota and SCFAs and their potential clinical significance and molecular mechanisms in HTGP.Materials and methodsThis study collected feces and serum samples from 18 HTGP patients and 18 healthy volunteers. We compared baseline clinical characteristics, gut microbiota diversity (via 16S rRNA sequencing), and serum SCFA concentrations (using mass spectrometry and other techniques) between the two groups to identify characteristic alterations. Correlation analyses explored associations between microbiota, metabolites, and clinical parameters. Further animal models validated the in vivo functions and molecular mechanisms of SCFAs.ResultsHTGP patients exhibited higher body mass index (BMI), triglyceride (TG) levels, metabolic complication incidence and disease severity scores. In addition, the gut microbiota showed significantly reduced richness and diversity in HTGP. Serum metabolomics analysis revealed significantly higher concentrations of isovaleric acid, decanoic acid and octanoic acid in HTGP patients, demonstrating good diagnostic value. Correlation analysis indicated that differential gut microbiota and metabolites were closely associated with clinical parameters. Animal experiments confirmed that butyrate can alleviate HTGP disease severity by inhibiting NF- κ B/NLRP3 pathway activation.DiscussionIn summary, this study identified differential gut microbiota and SCFAs in HTGP patients compared to healthy volunteers, and confirmed that butyrate exerts a protective effect through NF-κB/NLRP3 pathway.